Expansion of the 1st WHO international standard for antiserum to respiratory syncytial virus to include neutralisation titres against RSV subtype B: An international collaborative study. Issue 4 (22nd January 2020) - McDonald, Jacqueline U.; Rigsby, Peter; Atkinson, Eleanor; Engelhardt, Othmar G.; ,
Abstract: An International Standard to harmonise results from RSV subtype A neutralisation assays was generated and established by the World Health Organization in 2018. Here we report on a study to expand the use of that standard to include neutralisation assays using human sera against RSV subtype B and to test its ability to harmonise neutralisation titres from neutralisation assays including complement. The study included 11 laboratories from 6 countries. All participants used their own in-house virus neutralisation assay and their own virus stocks. The study samples comprised the current International Standard (16/284) and its potential replacement (16/322), individual sera from naturally infected humans, a monoclonal antibody to RSV (palivizumab) and samples from the BEI Resources panel of human antiserum and immune globulin to RSV. Of the 11 laboratories that took part in the study, 5 returned data from neutralisation assays with and without the inclusion of serum complement. The study showed that inter-laboratory variability in neutralisation titres was significantly reduced when values were expressed relative to 16/284 or 16/322. Complement did not affect the ability of the International Standard to decrease inter-laboratory variability as the standard was able to reduce the differences between titres from assays with and without complement. Based on these results, we will recommend to the WHO Expert Committee on Biological Standardisation (ECBS) that 16/284 and 16/322 be expanded in their use to include neutralisation assays against RSV/B.